Predicting outcome in older hospital patients with delirium: a systematic literature review. (24th August 2015) - Jackson, Thomas A; Wilson, Daisy; Richardson, Sarah; Lord, Janet M
Abstract : Objective: Delirium is a serious neuropsychiatric syndrome common in older hospitalised adults. It is associated with poor outcomes, however not all people with delirium have poor outcomes and the risk factors for adverse outcomes within this group are not well described. The objective was to report which predictors of outcome had been reported in the literature. Methods: We performed a systematic review by an initial electronic database search of MEDLINE, Embase and PsycINFO using four key search criteria. These were: (1) participants with a diagnosis of delirium, (2) clearly defined outcome measures, (3) a clearly defined variable as predictor of outcomes and (4) participants in the general hospital, rehabilitation and care home settings, excluding intensive care. Studies were then selected in a systematic fashion using specific predetermined criteria by three reviewers. Results: A total of 559 articles were screened, and 57 full text articles were assessed for eligibility. Twenty seven studies describing 18 different predictors of poor outcome were reported. The studies were rated by the Newcastle–Ottawa Score and were generally at low risk of bias. Four broad themes of predictor were identified; five delirium related predictors, two co‐morbid psychiatric illness related predictors, eight patient related predictors and three biomarker related predictors. The most numerously described and clinically important appear to be the duration of the delirium episode, a hypoactive motor subtype, delirium severity and pre‐existing psychiatric morbidity with dementia or depression. These are all associated with poorer delirium outcomes. Conclusion: Important predictors of poor outcomes in patients with delirium have been demonstrated. These could be used in clinical practice to focus direct management and guide discussions regarding prognosis. These results also demonstrate a number of key unknowns, where further research to explore delirium prognosis is recommended and is vital to improve understanding and management of this condition. Copyright © 2015 John Wiley & Sons, Ltd.